Invention and transfer of climate change mitigation technologies on a global scale: A study drawing on patent data - Antoine Dechezleprêtre; Matthieu Glachant; Nick Johnstone; Yann Ménière (Fondazione Eni Enrico Mattei (FEEM), 2009)
Climate Change ; Mitigation Technologies ; Patent Data
Keywords: Q5; Q55; 330; Umwelttechnik; Technischer Fortschritt; Technologietransfer; Patent; Welt